2003
DOI: 10.1530/eje.0.1480013
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) gene polymorphism and non-genetic factors with Graves' ophthalmopathy in European and Japanese populations

Abstract: Objective: The development and severity of Graves' ophthalmopathy (GO) may result from a complex interplay of genetic and environmental factors. The aim of this study was to investigate the association of cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) gene polymorphism and non-genetic factors (age, sex, cigarette smoking) with GO in two different populations, Polish-Caucasians and Japanese. Design: We investigated the distribution of CTLA-4 A49G polymorphism in 264 Caucasian patients with Graves' disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 35 publications
4
74
2
2
Order By: Relevance
“…29 Apart from NFKB1 genotypes, no other variables had a significant effect on the development of ophthalmopathy in Japanese GD patients, confirming our previous results. 30 Thus, the predisposing factors to ophthalmopathy in Japanese population remain to be established.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%
“…29 Apart from NFKB1 genotypes, no other variables had a significant effect on the development of ophthalmopathy in Japanese GD patients, confirming our previous results. 30 Thus, the predisposing factors to ophthalmopathy in Japanese population remain to be established.…”
Section: Nfkb1 Promoter Polymorphism In Graves' Disease a Kurylowicz mentioning
confidence: 99%
“…The susceptibility genes are human leucocyte antigen (HLA), GD-1, GD-2 and GD-3 [4] and cytotoxic T-lymphocyte associated molecule-4 (CTLA-4) [5][6][7]. It has been suggested that the CTLA-4 gene polymorphism plays an important role in the development of Graves' hyperthyroidism in various populations [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic susceptibility of these diseases is thought to be polygenic. It has been reported that major histocompatibility complex (MHC) gene [3,4], cytotoxic T lymphocyte antigen-4 (CTLA-4) gene [4][5][6], thyrotropin receptor (TSHR) gene [7], PTPN22 gene [8], CD40 gene [9,10], interferon-γ (IFN-γ) gene [11], tumor necrosis factor-α (TNF-α) gene [12,13] and interleukin-13 (IL-13) gene [14] polymorphisms are associated with GD and their interactions may influence disease phenotype and severity [3]. However, their contribution to susceptibility to GO awaits confirmation.…”
mentioning
confidence: 99%